2022
DOI: 10.24191/ji.v17i1.15876
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study on the Level of OSH Awareness Among UiTM Cawangan Pulau Pinang Staff

Abstract: Safety and health are important factors of any organization to ensure smooth and effective functioning. Occupational safety and health (OSH) awareness among the workers in the prevention of occupational injuries and illness. Various programmes have been implemented by the government and private organizations to increase the knowledge and awareness of OSH in the workplace including among institution higher learning staff in Malaysia. A study was undertaken to identify factors influencing the awareness level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Therefore, the company`s management must implement an OSH intervention programme to ensure all factors can be improved to a very high level. The findings of the present study support the findings of a recent study by Jaafar et al (2022), which found that the level of OSH awareness among non-academic staff in the workshop and laboratory of Universiti Teknologi MARA, Pulau Pinang, Malaysia is high, with an overall mean score of 4.41. The highest level of awareness factor is OSH policy with a mean score of 4.90, while the lowest awareness level is SHC with a mean score of 3.90.…”
Section: Osh Awareness Levelsupporting
confidence: 90%
“…Therefore, the company`s management must implement an OSH intervention programme to ensure all factors can be improved to a very high level. The findings of the present study support the findings of a recent study by Jaafar et al (2022), which found that the level of OSH awareness among non-academic staff in the workshop and laboratory of Universiti Teknologi MARA, Pulau Pinang, Malaysia is high, with an overall mean score of 4.41. The highest level of awareness factor is OSH policy with a mean score of 4.90, while the lowest awareness level is SHC with a mean score of 3.90.…”
Section: Osh Awareness Levelsupporting
confidence: 90%